Field experimental tests and analyses of suspension frame vibration of low-medium speed maglev train. Issue 2 (June 2023) - Ou, Fengyu; Liao, Xiaokang; Yi, Cai; Chen, Zili; Lin, Jianhui
Pushed by social demands, China has continuously developed its low-medium speed maglev transportation systems in recent decades. However, with the increase of the running mileage of the train, high frequency vibration of suspension frame gradually appears. In this paper, a method to analyze the high frequency vibration of suspension frame by detecting the current of traction motor is proposed. Field measurements of suspension frame vibration and traction motor current of low-medium maglev train were conducted on a maglev line that has been commercially put into operation. The test results show that the speed of the measured maglev train was closely correlated with vibration accelerations of the suspension frame in three directions, but as the speed increased, the influence it imposed on the suspension frame vibration waned. The dominant frequency of traction motor resultant current was consistent with the dominant frequency of the suspension frame vibration acceleration. The switching frequency of traction inverter was the main cause of high frequency vibration of suspension frame.